Tingkat Berpikir Kreatif Siswa dalam Menyelesaikan Masalah Matematika Berdasarkan Gaya Kognitif Reflektif dan Impulsif - Siti Rahmatina; Utari Sumarmo; Rahmah Johar (Universitas Syiah Kuala, 2014)
This study aims to determine the level of students' creative thinking in solving math problems. This study is a qualitative verificative research. Subjects numbered 4 people ie students of SMA Negeri 4 Banda Aceh class X. The selection of subjects was based on Matching Familiar Figure Test ( MFFT ) ie 2 students and 2 students reflective impulsive. The data were obtained from the study subjects written response tests of creative thinking math ( TBKM ) and interviews. To test the credibility of the data the researcher doing triangulation. In this study, triangulation was used to compare the triangulation method TBKM TBKM 1 with 2 and interviews. Creative thinking abilities of students can be seen by thinking of creative mathematics achievement indicators. Creative thinking ability of students surveyed as follows, the level of creative thinking on the subject of reflective material up 1 flat is level 4 which meets four indicators of fluency, novelty, flexibility, and elaboration, the level of creative thinking on the subject of reflective material equation 1 is a straight line that is level 4 meet four indicators fluency, novelty, flexibility, and elaboration. Level of creative thinking on the subject of reflective material up 2 flat is level 4 which meets four indicators of fluency, novelty, flexibility, and elaboration, the level of creative thinking on the subject of reflective material 2 is a straight line equation 4 level indicator which meets four fluency, novelty, flexibility, and elaboration. Level of creative thinking on the subject matter up impulsively 1 flat is level 1 which meet the proficiency indicator, the level of creative thinking on the subject matter impulsive equation 1 is a straight line which meets the level 1 two indicators of fluency and elaboration. Level of creative thinking on the subject matter up impulsively 2 flat is level 3 which meets three indicators of fluency, novelty, and elaboration, the level of creative thinking on the subject matter impulsive equation 2 is a straight line that meets two level 1 indicators fluency and elaboration.